'Confucianization of law' revisited. Issue 1 (2nd January 2021) - Zeng, Chi
ABSTRACT: The emphases of ritual, morality, and hierarchical relationships in imperial Chinese law are usually attributed to a process of "Confucianization of law" in Han dynasty. However, an interdisciplinary look at the notion of the 'Confucianization of law' from philosophical texts and legal materials will prove the vulnerability of such a simple conclusion. Philosophically, the Han dynasty saw first a politicization of Confucianism, which distinguished Han Confucianism from the Confucianism of previous generations. There was in fact a great contrast between Confucian ideals and Confucianization of law. Furthermore, by reading of Qin Law through the archeological material Shuihudi Qin Bamboo Texts, it can be seen that values we might label as Confucian existed already in Qin Law. These two considerations prove that simply attributing the moral and hierarchical characters of the imperial Chinese law to the single source of Confucianism does not do justice to the richness of the subject.